2015
DOI: 10.1137/130930984
|View full text |Cite
|
Sign up to set email alerts
|

New Doubling Spanners: Better and Simpler

Abstract: In a seminal STOC 1995 paper, Arya et al. conjectured that spanners for lowdimensional Euclidean spaces with constant maximum degree, hop-diameter O(log n), and lightness O(log n) (i.e., weight O(log n) · w(MST)) can be constructed in O(n log n) time. This conjecture, which became a central open question in this area, was resolved in the affirmative by Elkin and Solomon in STOC 2013. In fact, Elkin and Solomon proved that the conjecture of Arya et al. holds even in doubling metrics. However, Elkin and Solomon'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
63
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(63 citation statements)
references
References 17 publications
0
63
0
Order By: Relevance
“…In ICALP'13 Chan et al [14] showed that, in any doubling metric, one can build a (1 + ǫ)-spanner with constant degree and with logarithmic diameter and lightness, within O(n log n) time. A close examination of the construction of [14] shows that its lightness is dominated by the lightness of the standard net-tree spanner.…”
Section: Applicationsmentioning
confidence: 99%
See 3 more Smart Citations
“…In ICALP'13 Chan et al [14] showed that, in any doubling metric, one can build a (1 + ǫ)-spanner with constant degree and with logarithmic diameter and lightness, within O(n log n) time. A close examination of the construction of [14] shows that its lightness is dominated by the lightness of the standard net-tree spanner.…”
Section: Applicationsmentioning
confidence: 99%
“…A close examination of the construction of [14] shows that its lightness is dominated by the lightness of the standard net-tree spanner. Plugging Theorem 4.7 in the construction of [14] gives rise to a logarithmic improvement in the lightness bound, for snowflake doubling metrics. This result is summarized in the following statement.…”
Section: Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…They showed that a k-FT (1 + ϵ)-spanner with degree O(k 2 ), diameter O(log n) and lightness O(k 2 log n), can be built in time O(n log n + k 2 n). Observe that the upper bounds of [15,41,16] are far from the known lower bounds: degree O(k 2 ) versus Ω(k), lightness O(k 2 log n) versus Ω(k 2 ), and runtime O(n log n + k 2 n) versus Ω(n log n + kn). (See Table 1 for a reference.)…”
Section: Euclidean Spannersmentioning
confidence: 99%